THE HERO-EXILE AT VOLODYMYR BIRCHAK'S STORY “AGAINST THE LAW”: TRAGEDY OF PSYCHOLOGICAL BIFURCATION - Novak, S. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2021)
The article is devoted the analysis of the one of Volodymyr Birchak's historical stories. In research the problem “the governor and the people” is considered on the material of the story "Against the law". The special place is occupied here with a theme of search of socially-ethical prospect.